Doppelgänger dark energy: modified gravity with non-universal couplings after GW170817 - Amendola, Luca; Bettoni, Dario; Domènech Fuertes, Guillem (Arxiv, 2018)
Gravitational Wave (GW) astronomy severely narrowed down the theoretical space for scalar-tensor theories. We propose a new class of attractor models for Horndeski action in which GWs propagate at the speed of light in the nearby universe but not in the past. To do so we derive new solutions to the interacting dark sector in which the ratio of dark energy and dark matter remains constant, which we refer to as doppelg\"anger dark energy (DDE). We then remove the interaction between dark matter and dark energy by a suitable change of variables. The accelerated expansion that (we) baryons observe is due to a conformal coupling to the dark energy scalar field. We show how in this context it is possible to find a non trivial subset of solutions in which GWs propagate at the speed of light only at low red-shifts. The model is an attractor, thus reaching the limit
Gesehen am 05.12.2018